2000
DOI: 10.1007/s004210000279
|View full text |Cite
|
Sign up to set email alerts
|

The influence of experimental muscle pain on motor unit activity during low-level contraction

Abstract: In the present study we compared motor unit (MU) activity in a painful extensor carpi ulnaris (ECU) muscle to that of a pain-free control. According to the pain adaptation model the activity of the painful ECU muscle may be inhibited and its antagonist activity increased during wrist extension performed as a pre-defined low-force ramp. The pre-defined low force may then be maintained by increased activity in the pain-free synergist muscles such as the extensor carpi radialis (ECR) muscle. Nine females (31-47 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 26 publications
3
21
1
1
Order By: Relevance
“…Consistent with our findings, most previous studies (Sohn et al, 2000;Farina et al, 2005;Hodges et al, 2008) have shown decreased motor unit discharge rate during pain when force was maintained. Birch et al (2000) showed no change in discharge rate when averaged across the whole pool, but this could be explained by recruitment of new units and the increase in discharge rates of a few units as identified here.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Consistent with our findings, most previous studies (Sohn et al, 2000;Farina et al, 2005;Hodges et al, 2008) have shown decreased motor unit discharge rate during pain when force was maintained. Birch et al (2000) showed no change in discharge rate when averaged across the whole pool, but this could be explained by recruitment of new units and the increase in discharge rates of a few units as identified here.…”
Section: Discussionmentioning
confidence: 51%
“…Consistent with the pain adaptation theory, antagonist muscle activity is increased during pain in some (Arendt-Nielsen et al, 1996;Graven-Nielsen et al, 1997;Svensson et al, 1997;Falla et al, 2007) but not all (Calancie and Bawa, 1986;Birch et al, 2000;Falla et al, 2007) studies. However, to maintain force with decreased motor unit discharge, antagonist muscle activity must decrease.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…As a result, subjects were still able to sustain the same mean level of motor output in both conditions despite significant increases in fluctuations of task-related and tangential forces during painful compared with non-painful conditions. Although inconsistent with the homogeneous inhibition of agonist muscles predicted by the pain-adaptation model (Lund et al 1991), these results are supported by a number of studies which have also reported no pain-induced changes in EMG during static contractions (Graven-Nielsen et al 1997;Birch et al 2000;Hodges et al 2008). …”
Section: Pain-adaptation Strategymentioning
confidence: 67%
“…These levels of MVC were chosen because they represent the effort typically performed during most daily activities. 4,15 After a 20-second rest, a strap used to apply the wrist extension force was placed over the palm of the subjects' hand. The extension force was applied by weights, pulling via a cable at an angle 90°with the hand.…”
Section: Procedures Laboratory Setupmentioning
confidence: 99%